Răspuns :
√4x²+6x+3=x+2 .Ridici la patrat: ⇒4x²+6x+3=x²+4x+4
3x²+2x-1=0
Δ=4+4*1*3=16
x1= (-2+√16)/2=(-2+4)/2=2/2=1
x2=(-2-√16)/2=(-2-4)/2=-6/2=-3
3x²+2x-1=0
Δ=4+4*1*3=16
x1= (-2+√16)/2=(-2+4)/2=2/2=1
x2=(-2-√16)/2=(-2-4)/2=-6/2=-3
conditie rad = cu un numar pozitiv , deci x +2 ≥ 0 ; x ≥ - 2
⇒ solutia x ∈ [ -2 , + ∞ )
4x² + 6x + 3 = 0 cu Δ = 36 -4·4 ·3 = 36 - 48=-12 poz. pe R
rez. ec. : ridicam la patrat
4x² +6x +3 = x² + 4x + 4
3x² + 2x - 1 = 0 Δ =4 +12 =16
x₁ = ( -2 -4 ) / 2·3 = -6 / 6 = -1
x₂ = ( -2 + 4) / 2·3 = 2 / 2·3 = 1 / 3
S = { - 1 , 1 /3}
⇒ solutia x ∈ [ -2 , + ∞ )
4x² + 6x + 3 = 0 cu Δ = 36 -4·4 ·3 = 36 - 48=-12 poz. pe R
rez. ec. : ridicam la patrat
4x² +6x +3 = x² + 4x + 4
3x² + 2x - 1 = 0 Δ =4 +12 =16
x₁ = ( -2 -4 ) / 2·3 = -6 / 6 = -1
x₂ = ( -2 + 4) / 2·3 = 2 / 2·3 = 1 / 3
S = { - 1 , 1 /3}